Diphtheria, tetanus, and pertussis immunity among healthcare professionals and pregnant women in the Moscow region, Russian federation: A preliminary cross-sectional study - Basov, Artem A.; Zhernov, Yury V.; Kashutina, Maria I.; Kashkovskaya, Natalia N.; Kombarova, Svetlana Yu.; Enilenis, Inga I.; Severova, Lyudmila P.; Fadeeva, Inna A.; Vysochanskaya, Sonya O.; Belova, Elena V.; Shashina, Ekaterina A.; Makarova, Valentina V.; et al. (Frontiers in Pediatrics, 2023)
Despite more than 50 years of primary immunization against diphtheria, pertussis, and tetanus in Russia, complicated illnesses, including fatal ones, still occur. The goal of this preliminary cross-sectional study is to see how well pregnant women and healthcare workers are protected against diphtheria, pertussis, and tetanus. The required sample size (pregnant women and healthcare professionals, as well as pregnant women of two age categories) for this preliminary cross-sectional study was calculated using a confidence value of 0.95 and a probability of 0.05. The required number of participants in each group calculated sample size must be at least 59 people. In the Moscow region (Solnechnogorsk city, Russia), a cross-sectional study of pregnant patients and healthcare professionals interacting with children regularly as part of their job from numerous medical organizations was conducted in the year 2021 (n=655). Antibodies to diphtheria, tetanus, and pertussis toxoids and microorganisms were measured using an enzyme-linked immunosorbent assay (ELISA). The STATISTICA and IBM SPSS Statistics 26.0 were used to process the study results statistically. Descriptive statistics methods, the Mann-Whitney U-test, discriminant analysis with the stepwise selection and analysis of ROC-curves were applied. IgG against diphtheria was found in 99.5% of pregnant women, tetanus in 91.5%, and pertussis in only 36.5%. According to the results of the discriminant analysis, the value of IgG to pertussis is linked to the value of IgA to pertussis and the gestational periods. Immunity to diphtheria was discovered in 99.1% of medical personnel, tetanus in 96.9%, and pertussis in 43.9%, with no significant variations in age. When comparing the levels of immunity of pregnant women and healthcare professionals, it was shown that healthcare workers have greater levels of immunity against diphtheria and tetanus. Considering the data obtained from the preliminary cross-sectional study, we believe that it is necessary to conduct a full-scale study on a larger sample and, based on that, make certain changes to the national immunization program in Russia.